The Crown Lands Department, the Government, and the Settlers of McNab Township, Canada West - Vosburgh, Michelle (Ontario History, 2008)
After the 1837-38 rebellions, it was important to maintain public trust in government. At the same time people expected significant reforms and, ultimately, responsible government. The circumstances surrounding Archibald McNab and the settlers whom he had located in McNab Township in the 1830s and 1840s, highlight ways in which the transition to responsible government took form. The settlers, deceived and oppressed by McNab, became useful political tools and their plight was highly publicized by reformers. McNab came to represent the old ways of using position and power to further one’s own status and wealth while a new ideal of serving the public interest was moving to the fore. Because so many of the settlers’ problems stemmed from land distribution, the government had to handle the issue carefully. Encouraging settlement was the most important activity of the government in this period and its policies needed to apply consistently across Canada West in order to maintain trust and stability. Its handling of the difficulties in McNab was both consistent and flexible, raising no cries of special treatment.